A qualitative study on gender barriers to eye care access in Cambodia - Camille Neyhouser; Ingrid Quinn; Tessa Hillgrove; Renee Chan; Chhorvann Chhea; Seang Peou; Pol Sambath (BMC Ophthalmology, 2018)
Abstract Background The Fred Hollows Foundation (FHF) Cambodia recently partnered with the Ministry of Women’s Affairs (MoWA) and National Program for Eye Health (NPEH, part of the Ministry of Health) to establish the Gender Equality in Eye Health Project. As part of this project, a qualitative study was carried out to identify barriers affecting women’s access to eye health in Cambodia. Methods A cross-sectional qualitative study was conducted in four provinces in both urban and rural locations between May and June 2015. Purposive sampling was used to identify respondents from a range of age groups, geographical locations, and experiences to explore different perceptions regarding access barriers to eye health care. Thirteen women experiencing eye problems (age range 45–84 years; mean age 63 years) and 25 eye health professionals took part in in-depth interviews. Eleven focus groups discussions were held with 69 participants (50 women, 19 married men) to capture the views and experiences of both younger and older women, as well as household decision makers’ perspectives. Results Gender-based differences in decision-making, access and control over resources and women’s social status all contributed to impeding women’s access to eye health services. Women relied predominantly on informal sources of information about health, and these channels might be utilised to address barriers to information and access. Disparities in perceived costs of eye health treatment were evident between eye healthcare providers and users: costs were not perceived as a barrier by service providers due to health financing support for poor patients, however, many users were not aware of the availability of the scheme. Conclusion Demand-side and supply-side elements interact to reduce women’s ability to seek eye treatment.